The Transformation of Intrinsic Elements in The Adaptation of The Viscount Who Loved Me into TV - Sari Nur Rizki Fitria (Universitas Negeri Medan, 2025)
This study analyzes the transformation of intrinsic elements in The Viscount Who Loved Me novel into the TV series entitled Bridgerton Season 2 by Shondaland through the adaptation theory by Linda Hutcheon. Transformation in the adaptation process leads to the ideology contained in novel and TV series. Mythology by Roland Barthes is used to uncover the ideology behind the adaptation, and it will bring us to the motive of the adaptation. The data are in intrinsic elements such as character, characterization, and plot were taken from the texts in The Viscount Who Loved Me and the TV Series Bridgerton Season 2. The result of this study shows that there are differences in ideologies. In the novel, the ideologies are filled with patriarchy and social class, while in the TV series they focus on American values, feminism, and liberalism. These ideologies reflect the motives behind the adaptation, which are cultural capital and economic lure.